Effect of Organoclay on the Morphology, and Thermal Properties of Polystyrene/Poly (vinyl chloride) Nanocomposites - Aseeri, Jumaa; Mekhamer, Waffa; Alandis, Naser (Arab Journal for Sciences and Research Publishing, 2015)
Polystyrene and poly (vinyl chloride) (PS/PVC) were prepared via solvent casting method with different weight ratios of PS/PVC: (100/0, 90/10, 80/20, 10/90 and 0/100) to investigate their miscibility. We have studied the morphology of blend PS90/PVC10 (Pd1) with different content (1, 3, 10 %) of organoclay (MM). Cetylpyridinium chloride (CPC) is used to modify the clay sample after saturating its surface with Na+ ions. Fourier transform infrared (FTIR), X-ray diffraction (XRD), and transmission electron microscopy (TEM) were used to characterize the clay sample before and after modification by CPC. The blend miscibility has been confirmed by FTIR, XRD, differential scanning calorimetry (DSC) studies. The prepared nanocomposites were characterized using FTIR, DSC, TEM and scanning electron microscope (SEM). We observed that MM have a significant effect on improvement the miscibility of PS/PVC blends. The thermal stability of the nanocomposites was measured using thermogravimetric analysis (TGA).
Keywords: Organoclay; Morphology; Thermal Properties; Nanocomposites; Polystyrene/Poly; vinyl chloride